Check your vocabulary for Ielts - Wyatt, Rawdon (Macmillan, 2008)
This workbook features a range of activities to help students learn and revise vocabulary for the IELTS exam. Using exercises, word games, puzzles and quizzes, the book covers both general and topic-specific vocabulary as well as grammar, comprehension, pronunciation and spelling.